Minimal Detectable Change for TUG and TUDS Tests for Children With Down Syndrome. Issue 1 (January 2017) - Martin, Kathy; Natarus, Michael; Martin, Jeremy; Henderson, Sarah
Abstract : Purpose: To determine test-retest reliability and minimal detectable change of the Timed Up and Go (TUG) and Timed Up and Down Stairs (TUDS) for Down syndrome. Subjects: Twelve children with Down syndrome (DS) aged 3 to 17 years. Methods: Two sessions, 1 week apart, with 3 trials of the TUG and 2 trials of the TUDS. Test-retest reliability was estimated using intraclass correlation coefficients and the standard error of measurement. The minimal detectable changes (MDCs) for both tests were calculated. Results: The TUG and TUDS tests both had high test-retest reliability. The MDC was 1.26 seconds for the TUG and 12.52 seconds for the TUDS test. Conclusions: Both tests were reliable in this population, but the MDC results suggest only the TUG is clinically useful. Abstract : The goal of this study was to determine the test-retest reliability and minimal detectable change of the Timed Up and Go and Timed Up and Down Stairs tests in children and adolescents with Down syndrome.